WHEAT AS A SUMMER CROP IN THE HIGH VALLEYS OF MEXICO - RUPERT, J; ORTEGA, C; MARINO, ANTONIO; CAVAZOS, CARLOS G; BORLAUG, NE (Hospital General, CD MEXICO, DF, MEX, 1949)
Wheat was introduced into Mexico in 1521 by Cortez The most important commercial vars, with the exception of the recent introduction of Mentana from Italy, are of obscure origin Little is known of the history of the vars Candeal and Pelon Colorado (n
PHYS REV B
Keywords: WHEAT, SUMMER CROP, HIGH VALLEYS, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL